Moving the needle for COVID-19 vaccinations in Nigeria through leadership, accountability, and transparency - Ojeniyi, Toluwanimi; Eguavoen, Amenze; Chinye-Nwoko, Fejiro (Frontiers in Public Health, 2023)
The first set of vaccines arrived in Nigeria in March 2021. The National Primary Health Care Development Agency (NPHCDA) set out to vaccinate at least 70% percent of Nigeria's eligible population i.e., 111,776,503 people, by December 2022. As of June 2021, only 3% had received at least one dose of the vaccine. This presented a threat to the achievement of NPHCDA's goal. Nigeria Solidarity Support Fund (NSSF) went into a partnership with NPHCDA to accelerate the uptake of COVID-19 vaccinations across Nigeria over 3 months. Methods: Across Nigeria's 6 geopolitical zones, 6 states were selected, namely: Adamawa, Edo, Imo, Katsina, Nasarawa, and Ogun states based on performance, political will, and absence of external resources. A two-pronged approach was implemented: unrestricted funding to the sub-national level and providing technical support at the national level. Results: 5 out of 6 states received unrestricted funding to ramp up vaccination coverage. They also received adequate vaccine supplies. A total of 12,000 healthcare workers were trained on safe immunization practices and multiple communities were engaged across the 133 local government areas (LGAs) through religious and community leaders. After 6 months, there was an average of 35% increase in the uptake of COVID-19 vaccines in the 5 states. An indicator tracker was developed for weekly reviews at the national level and the total population vaccinated in Nigeria increased from 6,186,647 to 11,985,336 at the end of the partnership. Conclusion: Unrestricted funding, though not without its risks, can yield a significant impact on health. The intervention was co-designed with stakeholders and had leadership buy-in, accountability mechanisms, with unrestricted funding. These techniques produced an increase in the vaccination rates in the 5 states and across the country. These elements should be explored for application to other program designs such as routine immunization.